Activation of transcription factor circuity in 2i-induced ground state pluripotency is independent of repressive global epigenetic landscapes. Issue 14 (25th June 2020) - Shukla, Ruchi; Mjoseng, Heidi K; Thomson, John P; Kling, Simon; Sproul, Duncan; Dunican, Donncha S; Ramsahoye, Bernard; Wongtawan, Tuempong; Treindl, Fridolin; Templin, Markus F; Adams, Ian R; Pennings, Sari; et al.
Abstract: Mouse embryonic stem cells (mESCs) cultured with MEK/ERK and GSK3β (2i) inhibitors transition to ground state pluripotency. Gene expression changes, redistribution of histone H3K27me3 profiles and global DNA hypomethylation are hallmarks of 2i exposure, but it is unclear whether epigenetic alterations are required to achieve and maintain ground state or occur as an outcome of 2i signal induced changes. Here we show that ESCs with three epitypes, WT, constitutively methylated, or hypomethylated, all undergo comparable morphological, protein expression and transcriptome changes independently of global alterations of DNA methylation levels or changes in H3K27me3 profiles. Dazl and Fkbp6 expression are induced by 2i in all three epitypes, despite exhibiting hypermethylated promoters in constitutively methylated ESCs. We identify a number of activated gene promoters that undergo 2i dependent loss of H3K27me3 in all three epitypes, however genetic and pharmaceutical inhibition experiments show that H3K27me3 is not required for their silencing in non-2i conditions. By separating and defining their contributions, our data suggest that repressive epigenetic systems play minor roles in mESC self-renewal and naïve ground state establishment by core sets of dominant pluripotency associated transcription factor networks, which operate independently from these epigenetic processes.